Reducing Anxiety in Pediatric Circumcision Using an Affective-Based Virtual Reality: A Pre-Post Experimental - Zaenal Abidin; Abas Setiawan; Sri Ratna Rahayu; Bertakalswa Hermawati (Jurnal Kesehatan Masyarakat, 2026)
Anxiety is a common emotional response among children undergoing invasive medical procedures such as circumcision, which can compromise procedural comfort and increase resistance. This study aimed to evaluate the effectiveness of a space adventure-themed Virtual Reality (VR) application as a distraction medium to reduce anxiety in boys during circumcision procedures. It involved 26 children aged 10–14 who participated in this study. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI-T) instrument before and after the intervention. The application was designed using an Affective Virtual Reality methodology, which integrates emotional elements and immersive experiences into a virtual environment to create a relaxed and enjoyable atmosphere. VR was used during the procedure to distract children from painful and fearful stimuli. The results showed decreased anxiety levels after the intervention, indicating that VR technology is effective as a non-pharmacological distraction strategy in clinical contexts. These findings contribute to the use of immersive technology as an innovative approach to supporting children’s psychological comfort during medical procedures and open opportunities for developing similar interventions in other pediatric medical contexts.